Joint predictors of antenatal care contacts and timing of antenatal care initiation among women of reproductive age in Ethiopia - Abebew Aklog Asmare; Awoke Seyoum Tegegne; Denekew Bitew Belay (PLoS ONE, 2025)
Background Maternal and neonatal mortality remain major public health challenges, particularly in low-income countries like Ethiopia. Antenatal care (ANC) plays a vital role in improving maternal and neonatal outcomes. This study aimed to jointly assess the predictors of ANC contacts (defined as a woman receiving four or more contacts during pregnancy) and timing of ANC initiation (defined as a woman starting ANC early (during the first trimester)) using a bivariate binary logistic regression model. Methods Data were drawn from the 2019 Ethiopian Mini Demographic and Health Survey (EMDHS), conducted by the measures of the DHS Program. A total of 5,492 weighted women aged 15–49 years with recent births were included. A bivariate binary logistic regression model was employed to simultaneously examine the two ANC outcomes, taking into account their potential interdependence. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported. Results The prevalence of completing four or more ANC visits and timely ANC initiation was 59.7% and 19.8%, respectively. Among 5,492 ever-married women, timely ANC initiation and completing four or more ANC visits were significantly associated. Maternal age, region, maternal education, wealth index, and number of children ever born were identified as joint predictors affecting both outcomes. For example, compared to women from poor households, those from middle-income households had higher odds of receiving four or more ANC contacts (AOR = 1.391; 95% CI: 1.121–1.726) and initiating ANC early (AOR = 2.047; 95% CI: 1.669–2.511). Conclusion The findings highlight significant socioeconomic and geographic disparities in ANC utilization in Ethiopia. Integrating both outcomes into a joint modeling framework provides a more comprehensive understanding of maternal health service use. Targeted interventions are needed to promote early and adequate ANC, particularly among poor and rural populations.